Nicaragua and the politics of utopia development and culture in the modern stat - Chávez, Daniel (Nashville Vanderbilt University Press, 2015)
"Nicaragua and the Politics of Utopia proposes that utopias are not only for novelists and poets; contemporary dictators, Marxist revolutionaries, and neoliberal economists also deal with promises and hubris, with imagined national destinies that often end up in conflict and disaster" -- Provided by publisher.
Includes bibliographical references and index.
Keywords: Politics and literature--Nicaragua--History--20th century